2016
DOI: 10.1186/s12951-016-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity assessment of CdSe/ZnS quantum dots in macrophages, lymphocytes and BALB/c mice

Abstract: BackgroundThe toxicity of CdSe/ZnS quantum dots (QDs) in the environment and biological systems has become a major concern for the nanoparticle community. However, the potential toxicity of QDs on immune cells and its corresponding immune functions remains poorly understood. In this study, we investigated the immunotoxicity of CdSe/ZnS QDs using the in vitro in macrophages and lymphocytes and in vivo in BALB/c mice.ResultsOur results indicated that macrophages treated with 1.25 or 2.5 nM QDs exhibited decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…2b). The result showed that the QDs had no obvious effect on the organ indexes, which was consistent with our Immunotoxicity assessment study of CdSe/ZnS on BABL/c mice20. Since we wanted to study the reproductive toxicity of QDs for female mice, the organ index of ovary was recorded as well but no obvious difference was detected between the control and treated groups (Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…2b). The result showed that the QDs had no obvious effect on the organ indexes, which was consistent with our Immunotoxicity assessment study of CdSe/ZnS on BABL/c mice20. Since we wanted to study the reproductive toxicity of QDs for female mice, the organ index of ovary was recorded as well but no obvious difference was detected between the control and treated groups (Fig.…”
Section: Resultssupporting
confidence: 84%
“…20 years2223. The accumulation of QDs were mainly found in reticuloendothelial system (RES) organs, such as liver and spleen2024.…”
Section: Resultsmentioning
confidence: 99%
“…For example, exposure to CdSe/ZnS QDs induced a decrease in the population of T lymphocytes and an increase in the population of B lymphocytes, but had no effect on the population of NK cells in mice exposed for 42 days [28]. On the other hand, Fu et al observed that titanium dioxide NPs (nano-TiO 2 ) induced proliferation of B and T lymphocytes after continued exposure for 4 weeks [29].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of the immune system, the toxicity assessment of NPs relies on overall changes of immune cytokines and molecules, immune organs, hematological system, etc. For instance, the generation and release of ILs and tumor necrosis factors are usually examined upon the use of NPs at high aspect ratio, some metal or certain cationic [97,98]. Histological changes of major immune organs (e.g.…”
Section: Immune and Reproductive Systemmentioning
confidence: 99%
“…Histological changes of major immune organs (e.g. spleen) are preferably observed by H&E dyeing [97,99].…”
Section: Immune and Reproductive Systemmentioning
confidence: 99%